LncRNA SLCO4A1-AS1 Accelerates Growth and Metastasis of Gastric Cancer via Regulation of the miR-149/XIAP Axis - Fang, Yantian; Sun, Bo; Gao, Jianpeng; Huang, Yakai; Wang, Chenchen (Frontiers in Oncology, 2021)
Objective: Recently, long noncoding RNA SLCO4A1 antisense RNA 1 (SLCO4A1-AS1) has been shown to act as an oncogene in several cancer types; however, its role in gastric cancer (GC) and its underlying molecular mechanisms are yet to be elucidated. Methods: Using the ENCORI database, we identified SLCO4A1-AS1, miR-149-5p (miR-149), and the X-linked inhibitor of apoptosis (XIAP) whose expressions were obviously changed in GC samples, and analyzed the correlation between their expressions in GC samples. Moreover, we explored the expression of SLCO4A1-AS1, miR-149, and XIAP in clinical samples and GC cell lines using RT-qPCR and western blotting assay; the correlation between them was analyzed using RNA immunoprecipitation and dual-luciferase reporter. CCK-8, colony formation, and Transwell assays were conducted to determine the effects of SLCO4A1-AS1, miR-149, and XIAP expression on cell proliferation, migration, and invasion, respectively. A nude mouse xenograft model was used to explore their function in xenograft growth. Results: SLCO4A1-AS1 was significantly upregulated in the GC samples and cell lines, and a high level of SLCO4A1-AS1 was associated with an advanced tumor stage and shortened patient survival. Mechanistically, SLCO4A1-AS1 post-transcriptionally regulated XIAP by functioning as competing endogenous RNA in GC to sponge miR-149. Further functional assays revealed that the overexpression of miR-149 and knockdown of XIAP considerably inhibited GC cell viability and its migratory and invasive characteristics in vitro. SLCO4A1-AS1 knockdown also determined the function of GC cells but was diminished by the miR-149 inhibitor in vitro. Finally, we demonstrated that the deletion of SLCO4A1-AS1 suppressed tumor growth and metastasis in vivo. Conclusions: Altogether, these findings suggest that SLCO4A1-AS1 functions as a crucial oncogenic lncRNA in GC and it can facilitate GC tumor growth and metastasis by interacting with miR-149 and enhancing XIAP expression. Therefore, SLCO4A1-AS1 is a potential novel therapeutic target in GC treatment.